Sex Discrimination in Uncertain Times - Thornton, Margaret (ANU Press, 2010)
This collection of essays arose from a conference held to mark the silver anniversary of the Australian Sex Discrimination Act (1984). The collection has two aims: first; to honour the contributions of both the spirited individuals who valiantly fought for the enactment of the legislation against the odds, and those who championed the new law once it was passed; secondly, to present a stock-take of the Act within the changed socio-political environment of the 21st century. The contributors present clear-eyed appraisals of the legislation, in addition to considering new forms of legal regulation, such as Equality Act, and the significance of a Human Rights Act. The introduction of a proactive model, which would impose positive duties on organisations, is explored as an alternative to the existing individual complaint-based model of legislation. The contributors also pay attention to the international human rights framework, particularly the Convention on the Elimination of all Forms of Discrimination against Women and the UN Declaration on the Rights of Indigenous People. The essays are illuminated by recourse to a rich vein of historical and contemporary literature. Regard is also paid to the comparative experience of other jurisdictions, particularly the UK and Canada.